2018
DOI: 10.2478/jcbtp-2018-0028
|View full text |Cite
|
Sign up to set email alerts
|

Are Capital Ratios Procyclical? Evidence from Turkish Banking Data

Abstract: This paper contributes to the literature by providing recent empirical evidence about the positioning of the capital adequacy ratios (Basel II capital adequacy ratio and leverage ratio as proposed by Basel III) of Turkish banks and the business cycle. As in many emerging countries, the Turkish real sector is highly dependent on the banking loans for financing, and consequently, the macroeconomic system is vulnerable to the supply of bank loans. The results reveal that the Basel II capital adequacy ratio of Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Some studies found that bank's capital buffers acting counter-cyclically. This indicates that banks tend to boost their capital in normal times to be drawn during weak economic conditions (Turguttopbas, 2018). According to Mahdi and Abbes (2018), the undeveloped Islamic financial market forces Islamic banks in particular to keep larger capitals because it is challenging for them to raise money.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies found that bank's capital buffers acting counter-cyclically. This indicates that banks tend to boost their capital in normal times to be drawn during weak economic conditions (Turguttopbas, 2018). According to Mahdi and Abbes (2018), the undeveloped Islamic financial market forces Islamic banks in particular to keep larger capitals because it is challenging for them to raise money.…”
Section: Literature Reviewmentioning
confidence: 99%